The Effect of Training and Industrial Relations on Work Productivity That Impact on Employee Achievement at PT Barawaja Steel in Makasar - Daeli, Hasrat Putera Damai (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to determine the effect of training and industrial relations on work productivity which has an impact on employee performance at PT Barawaja Steel in Makassar. The method used is explanatory research with a sample of 94 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study showed that training had a significant effect on work productivity of 36.6%, hypothesis testing obtained a significance of 0.000 <0.05. Industrial relations have a significant effect on work productivity of 45.8%, the hypothesis test obtained a significance of 0.000 < 0.05. Training and industrial relations simultaneously have a significant effect on work productivity by 52.4%, hypothesis testing obtained a significance of 0.000 <0.05.